Saving the Earth - Anna Claybourne (United Kingdom Miles Kelly Publishing Ltd, 2015)
Discover which animals are losing their habitats, and how we can reduce pollution. 100 facts accompanied by detailed photographs and beautiful artwork will challenge children, acting as an incentive as they make their way through the book.
Keywords: Non-fiction -- Non-fiction